Studies on Removal of Emerging Endocrine Disruptor Compounds from Aqueous Phase by Synthesized Nanozeolites - Goyal, Nitin (My University, 2018)
Endocrine disruptor compounds (EDCs) are exogenous chemicals that interfere with the endocrine (hormone regulating) system by mimicking or blocking natural hormones of exposed organisms, even at trace amounts (1-10 mg/L). Thus, endocrine disruptor compounds have raised serious public and environmental concerns due to their ability of obstruction in the functioning of endocrinological systems. Endocrine disruptor compounds have certain binding affinity with cell membrane receptors due to structure similarity with natural hormone and their active metabolites, to mimic estrogenic mediated processes. Certain EDCs are characterized as emerging contaminants, which include biochanin A, genistein, daidzein, coumestrol and bisphenol S. In this thesis, five different types of nano-zeolites (NaA, NaX, NaY, beta and ZSM-5) were synthesized, characterized and then employed for the effective removal of these emerging endocrine disruptor compounds from aqueous phase. Nano-zeolites were simply synthesized by hydrothermal treatment with and without using organic template depending on the particular nano-zeolite. In characterization of nano-zeolites, the alignments of particles in adsorbent were observed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) micrographs. The elemental phase and composition were analyzed by X-ray diffraction (XRD) patterns and EDS, respectively. The surface functional groups and physical parameters of adsorbent were characterized by FT-IR and Brunauer-Emmett-Teller (BET), respectively. The surface charge and stability of nano-zeolites were measured by point of zero charge. The batch adsorption process was used to study various parameters such as pH (2-12), temperature (20-55°C), adsorbent dose (0.1-2 g/L), stirring speed (50-300 rpm), contact time (15-420 min) and initial adsorbate concentration (1-30 mg/L) for endocrine disrupting compounds from aqueous phase by nano-zeolites. Solution pH and initial adsorbate concentration had an important impact on EDCs adsorption onto prepared nano-zeolites with optimal removal (90–95%). To test the nature of adsorption weather it shows monolayer, multilayer, physical and chemical behavior it was analyzed by Langmuir, Freundlich, Temkin, Redlich-Peterson, Dubinin-Radushkevich and Harkins-Jura models. To verify the rate-controlling step whether it is physical adsorption, chemical interactions, bulk diffusion, film diffusion or mass transfer mechanism, the kinetic data of EDCs removal by the nano-zeolites were analyzed by three different models pseudo-first order model, pseudo-second order model and intra-particle diffusion model. The feasibility, orientation and spontaneity of EDC adsorption system was predicted by the thermodynamic parameters such as the standard free energy change (ΔG°), standard entropy change (ΔS°) and standard enthalpy change (ΔH°). Disposal study of EDC loaded nano-zeolite was also performed by incineration method and then existence of EDC onto nano-zeolite was analyzed by high performance liquid chromatography.
Keywords: Endocrine disruptor compounds; Nanozeolites; Synthesis; Characterization; Adsorption; Equilibrium; Kinetics; Thermodynamics; Disposal study